PEDAGOGY-PSYCHOLOGICAL ASPECTS OF EDUCATING SCHOOLCHILDREN IN THE SPIRIT OF PATRIOTISM (American Journal of Research in Humanities and Social Sciences, 2023)
This article is devoted to the pedagogy and psychological aspects of educating schoolchildren in the spirit of patriotism. The author pays special attention to the psychological aspects of the patriotic education of schoolchildren.